Kecerdasan Emosional Siswa Anggota â€œGengâ€ - hamamah, Vatin (Indonesian Journal of Guidance and Counseling: Theory and Application, 2017)
During adolescence many formed groups of peers as personal and social adjusment container teenagers, one of which is gangs. The existence of gangs can provide a positive and negative impact. It depends on the emotional intelligence of students have gang members. The purpose of this research is to describe emotional intelligence students of the gang of class XI-IIS.3 in SMA Kesatrian 2 Semarang. The type research used in this research is descriptive quantitative research. The population in this research were all students of class XI-IIS in SMA Kesatrian 2 Semarang. The sampling technique used is purposive sampling. Method of data collection used is the psychological scale. Data analysis used is percentage descriptive analysis. The results showed that the average emotional intelligence students of the gang classified in the medium category (65.87%). Based on the results of the research, the advice is for BK teachers, expected to provide services related to recognizing emotions, managing emotions, motivating oneself, recognizing emotions in others and build relationship. For example, through better information services so that students know and understand about recognizing emotions, managing emotions, motivating oneself, recognizing emotions in others and build relationship.